Risk management in commodities supply chains: from conceptual complexity to managerial practice - Pimpão, Marco André Viana Diniz (2018)
Over the past couple of decades, a long list of events has brought supply chain risk to the main stage of supply chain management literature, both academic and professional. More importantly, supply chain risk is now a daily concern for supply chain managers who see their global supply chains exposed to an endless list of potential causes for disturbances. Although the literature on supply chain risk management has increased enormously in past few years, there are only a handful of researchers who have addressed the topic in the context of commodities supply chains. Furthermore, most of the research that does address risk in commodities supply chains does so by focusing on commodities price risk. This thesis addresses commodities supply risk management with a view to establishing whether commodity price risk is the indeed the most relevant risk, as the attention it receives seems to suggest. It does so by using the example of steel supply chains and trying to establish which risks are the most relevant from the point of view of companies that are considered major steel buyers. With that purpose in mind, interviews have been carried out in two groups of companies - a multi-sector group and group of companies that are major steel buyers – to ascertain which supply risks are the most relevant for those companies and how they deal with those risks. Using those two groups a comparative analysis is carried out. Having carried out an extensive literature review and benefiting from the insights provided by the interviews, this research suggests that the complexity of the concepts involved, some confusion created by the different risk classifications in the literature and the lack of knowledge in important issues with an impact on risk are detrimental to the practical usefulness of theory, from a managerial point of view. With that concern in mind, this thesis suggests a framework for systematic supply risk management that incorporates a different approach to supply risk identification as its first step. This framework aims at being a practical tool to assist supply chain managers in their decision-making process.